The electrocardiogram signal automatic analysis: Fiducial points detection and change representation of the ST segment - Li, X.Y.; Wang, T.; Zhou, P.; Feng, H.Q. (International Journal of Computer Science in Sport, 2002)
ST-T complex of electrocardiogram (ECG) signal reflects an important phase of the ventricular repolarization. Many efforts have been made towards the ST-T analysis because of its clinical significance in diagnosing myocardial ischemia, infarction, etc. However, the identification of the ST segment fiducial points has not been standardized yet. The most often used time domain based methods are mainly empirically dependent and noise sensitive. In this research, ST-T complex automatic analysis including fiducial point detection and change representation of the ECG signals was investigated in the wavelet transform domain.